Posted by
**Chelsea** on
.

Differentiate.

y= (cos x)^x

u= cos x

du= -sin x dx

ln y = ln(cos x)^x

ln y = x ln(cos x)

(dy/dx)/(y)= ln(cos x)

(dy/dx)= y ln(cos x)

= (cos x)^x * (ln cos x)

(dx/du)= x(cos x)^(x-1) * (-sin x)

= - x sin(x)cos^(x-1)(x)

(dy/dx)-(dx/du)= [(cos^x(x))(ln(cos(x)))-(x sin(x)cos^(x-1)(x)]

(dy/du)= cos^x(x)*(ln(cos(x)))-(x tan(x))

Is this correct?

Also, I am stuck on a different problem.

Differentiate.

y= arctan(arcsin(sqrt(x)))

u= arcsin(sqrt(x))

du= (1/(sqrt(1-x^2))) dx

ln y = ln ?? do I put the whole original here?